2018
DOI: 10.17755/esosder.311314
|View full text |Cite
|
Sign up to set email alerts
|

Li̇se Öğrenci̇leri̇ni̇n Di̇ji̇tal Bağimliliklarinin İncelenmesi̇: Ankara İli̇, Çankaya İlçesi̇ Örneği̇

Abstract: Bu araştırmanın amacı, lise öğrencilerinin dijital bağımlılık düzeylerini belirlemektir. Araştırma, 2015-16 eğitim-öğretim yılında Çankaya ilçesinde yer alan lise öğrencileri üzerinde yapılmıştır. Çalışma grubunu Çankaya ilçesinden yer alan liselerden rastgele seçilen 828 öğrenci oluşturmaktadır. Bu araştırmanın verileri "Dijital Bağımlılık Ölçeği" ile toplanmıştır. Yapılan güvenilirlik analizi sonucunda cronbach alfa değeri 0.905 olarak bulunmuştur. Öğrencilerin dijital bağımlılık ve alt boyutlarına ilişkin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
1
16
0
8
Order By: Relevance
“…It is seen that the average score of game addiction of male students is higher than female students. When the literature is examined, there are studies that are in line with the findings of the study (Lucas & Sherry, 2004;Huanhuan & Su, 2013;Irles & Gomis, 2015;Aydın & Horzum, 2015;Çavuş, Ayhan, & Tuncer, 2016;Eni, 2017;Aktaş, 2018;Bülbül, Tunç, & Aydil, 2018;Dursun & Eraslan-Çapan, 2018;Eryılmaz & Çukurluöz, 2018;Göldağ, 2018;Kurtbeyoğlu, 2018;Oral, 2018;Taylan, Topal, & Ayas, 2018;Yavuz, 2018). There are studies in the literature that do not find a significant relationship between gender and digital game addiction (Hsu, Wen, & Wu, 2009;Taş, Eker, & Anlı, 2014;Öncel & Tekin, 2015).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is seen that the average score of game addiction of male students is higher than female students. When the literature is examined, there are studies that are in line with the findings of the study (Lucas & Sherry, 2004;Huanhuan & Su, 2013;Irles & Gomis, 2015;Aydın & Horzum, 2015;Çavuş, Ayhan, & Tuncer, 2016;Eni, 2017;Aktaş, 2018;Bülbül, Tunç, & Aydil, 2018;Dursun & Eraslan-Çapan, 2018;Eryılmaz & Çukurluöz, 2018;Göldağ, 2018;Kurtbeyoğlu, 2018;Oral, 2018;Taylan, Topal, & Ayas, 2018;Yavuz, 2018). There are studies in the literature that do not find a significant relationship between gender and digital game addiction (Hsu, Wen, & Wu, 2009;Taş, Eker, & Anlı, 2014;Öncel & Tekin, 2015).…”
Section: Discussionmentioning
confidence: 74%
“…As the class level increases, the circle of friends expands, close friendships are established so that students may prefer to spend time with friends instead of digital games. However, studies that have obtained different results have been found in the literature review (Eryılmaz & Çukurluöz, 2018). One of the important results of the study is that there is a statistically significant difference between the communication skill levels of the students according to the classes they study.…”
Section: Discussionmentioning
confidence: 96%
“…There are also studies in the literature with different results. In the study of Eryılmaz and Çukurluöz (2018), grade level does not have an effect that would make a significant difference on students' internet addiction averages. According to the research results of Kayri and Günüç (2016) aiming to determine the relationship between students 'internet addiction levels and students' economic levels, it was concluded that students with better economic status have higher addiction levels than those with lower levels.…”
Section: Conclusion and Recommendationsmentioning
confidence: 88%
“…Dijital bağımlılık, dijital çağda kitle iletişim araçları ile de bütünleşen dijital teknolojilerin bir sonucu olarak yaygınlık kazanmış (Arslan vd., 2015) ve internet bağımlılığı, dijital bağımlılık, teknolojik bağımlılık dijital oyun bağımlılığı ve akıllı telefon bağımlılığı perspektiflerinden Türkçe literatürde de çok sayıda araştırmacının üzerinde durduğu bir konu olmuştur (Köksal, 2015;Gezgin & Kaplan Akıllı, 2016;Savcı & Aysan, 2017;Eryılmaz & Çukurluöz, 2018). Araştırma sonuçlarına göre bu bağımlılığın temelinde yatan neden, davranışı gerçekleştirirken beynimizin sinir-bilişsel ödüller alıyor olmasıdır.…”
Section: Dijital Bağımlılıkunclassified